A nutrient method for cutivation of macroalgae Ulva papenfussii - Trung, Vo Thanh; Huynh, Tran Van; Duc, Tran Mai; Thinh, Phan Duc; San, Pham Trung; Hang, Nguyen Thanh (Academia Journal of Biology, 2019)
Macroalgae species of the genus Ulva are widely distributed in the wild. Many species of this genus has been used as food as an attractive material for the study of materials, fuels, food etc.. In this paper, we are focusing on nutrient method for cultivation of Ulva papenfussii and A nutrient source for cultivation of U. papenfussii was also investigated with the perspective of utilizing the produced biomass for feed. U. papenfussii is fragmented into 1 × 1 cm size, then it keep in Ulva extract of 0.1 g/l concentrate for 7 days. Then continue to keep fragments in the following conditions: 20 ml/l of PES medium, 700 μmol photon/m2/s of light, 25oC of temperature, 3% of salinity, 28 days of time. Under this condition the productivity U. papenfussii was 17.8 g/l of weight and its growth rate was 4.3–6.5% day. Nutritional cultivation is successful for U. papenfussii speceies, which is of great importance to study the potential of producing seaweed varieties like blades for commercial application of seaweed species.